Identification of Key Variables in the Utilization of Medicinal Ethnobotanical in KPHP Limau Unit VII Hulu Sarolangun - Lubis, Rizky Febriana Br; Zuhriansah, Alfi Laila; Juramang, Risnayanti R.; Safitri, Ikraeni; Marpaung, Sutan Sahala Muda (Jurnal Pijar Mipa, 2025)
The ethnobotanical utilization of medicinal plants is an integral part of the local wisdom of the Penguluh Tribe community in KPHP Limau Unit VII Hulu Sarolangun, Jambi. However, the lack of systematic documentation of key variables hampers efforts to preserve and develop this practice. This study aims to identify key variables that play a role in the sustainability of medicinal ethnobotany utilization. The methods used include primary data collection through in-depth interviews with stakeholders, literature reviews, and analysis of relationships between variables using the MICMAC (Matrix of Cross-Impact Multiplication Applied to Classification) approach. The results of the study show that of the 15 variables analyzed, seven main variables, such as regulation, types of medicinal plants, cultivation techniques, sources of knowledge, social roles, conservation efforts, and integration of local and formal learning, have a significant influence on the medicinal ethnobotany utilization system. The regulatory variable is identified as the key factor with the highest impact. The discussion highlights the importance of managing driver and linkage variables to ensure system sustainability. In conclusion, strengthening regulations, conservation of natural resources, and integrating local knowledge with scientific approaches are needed to strengthen medicinal ethnobotany and sustain local communities' welfare.